2023
DOI: 10.1186/s12935-023-02873-2
|View full text |Cite
|
Sign up to set email alerts
|

The addition of arginine deiminase potentiates Mithramycin A-induced cell death in patient-derived glioblastoma cells via ATF4 and cytochrome C

Abstract: Background Arginine auxotrophy constitutes a shortcoming for ~ 30% of glioblastoma multiforme (GBM). Indeed, arginine-depleting therapy using arginine deiminase from Streptococcus pyogenes (SpyADI) has proven activity against GBM in preclinical studies. The good safety profile of SpyADI renders this agent an ideal combination partner for cytostatic therapy. Methods In this study, we combined the antineoplastic antibiotic Mithramycin A (MitA) with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The assessment hinges on the results of an ex vivo chemosensitivity assay, which measures alterations in tumor morphology, cell viability through hematoxylin and eosin (H&E) staining, proliferative activity via Ki67 immunostaining, and apoptosis induction as evidenced by cleaved Caspase-3 staining. These observations are congruent with findings reported in the literature. In the course of our investigation, we discerned two distinct groups of glioma patients differentiated by their response to Mit-A. This bifurcation was facilitated by a proprietary algorithm that computes an M-score, incorporating data from the functional assays described above.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The assessment hinges on the results of an ex vivo chemosensitivity assay, which measures alterations in tumor morphology, cell viability through hematoxylin and eosin (H&E) staining, proliferative activity via Ki67 immunostaining, and apoptosis induction as evidenced by cleaved Caspase-3 staining. These observations are congruent with findings reported in the literature. In the course of our investigation, we discerned two distinct groups of glioma patients differentiated by their response to Mit-A. This bifurcation was facilitated by a proprietary algorithm that computes an M-score, incorporating data from the functional assays described above.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, all Mit-A-responsive patients were observed orienting toward high-grade glioblastomas; this aligns with recent findings which reported that Mit-A inhibits GBM invasiveness in patient-derived high-grade gliomas. 21,22 Moreover, the IDH1 mutation status of the tumor significantly complemented the M-score, suggesting a positive correlation between wild-type IDH1 status and response in the ex vivo setting. This finding contrasts with previous reports that posited Mit-A as a potent inhibitor for IDH mutant high-grade gliomas.…”
Section: ■ Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Combining SpyADI with Mithramycin A was found to be superior to sequential application, resulting in the enhanced impairment of colony formation, induction of senescence, and an increase iin mitochondrial membrane polarization and autophagy in glioma cells in vitro. Despite its promise for glioma treatment, more research is needed to evaluate its efficacy, safety, and dosing on other cancer types [85][86][87][88][89]. NEI-01 is another novel ADI-based drug that selectively depletes arginine in tumor cells to induce metabolic stress and cell death.…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%